Cellular and biomolecular mechanics and mechanobiology - Gefen, Amit (Studies in mechanobiology, tissue engineering and biomaterials, 2011)
This book describes these exciting new developments, and presents experimental and computational findings that altogether describe the frontier of knowledge in cellular and biomolecular mechanics, and the biological implications, in health and disease. The book is written for bioengineers with interest in cellular mechanics, for biophysicists, biochemists, medical researchers and all other professionals with interest in how cells produce and respond to mechanical loads.